Komunikasi Strategis Public Relations dan Praktik Account Management dalam Mendukung Transformasi Digital di Sektor Publik - Ninoy Amelia; Umaimah Wahid (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Digital transformation in the public sector requires the synergy of technology and effective communication to ensure that innovations such as the Satu Data Indonesia (SDI) system are accepted and optimally implemented by government institutions. This study aims to analyze the implementation and challenges of strategic public relations communication and account management practices in supporting digital transformation in the public sector through a case study of the SDI system by PT Telkom Indonesia. The theories used in this research include Excellence Theory, Digital Transformation Theory, and Strategic Communication Theory. This study employs a qualitative case study method. The findings reveal that PT Telkom Indonesia applies strategic communication and account management practices in an integrated, adaptive manner based on the specific needs of each institution to support digital transformation through the SDI program. However, the implementation faces multidimensional challenges such as digital literacy gaps, bureaucratic resistance, and disparities in infrastructure and human resources, which are addressed through educational, collaborative, and contextual communication approaches.